FgGyp8 as a putative FgRab1 GAP is required for growth and pathogenesis by regulating FgSnc1-mediated secretory vesicles fusion in Fusarium graminearum - Xing-zhi ZHANG; Shuang CHEN; Yakubu Saddeeq ABUBAKAR; Xu-zhao MAO; Peng-fei MIAO; Zong-hua WANG; Jie ZHOU; Hua-wei ZHENG (Journal of Integrative Agriculture, 2023)
Fusarium graminearum is an important plant pathogenic fungus that causes disease and yield reduction in many cereal crops, such as wheat and barley. Gyp8 stimulates GTP hydrolysis on Ypt1 in yeast. However, the functions of Gyp8 in plant pathogenic fungi are still unknown. In this study, we investigated the roles of FgGyp8 in F. graminearum by genetic and pathological analyses. Through gene knockout and phenotypic analyses, we found that FgGyp8 is required for vegetative growth in F. graminearum. The conidiation, conidial size and number of septa per conidium of ΔFggyp8 mutant are significantly reduced when compared to the wild type PH-1. Furthermore, FgGyp8 is crucial for pathogenicity on wheat coleoptiles and wheat heads. FgGyp8 contains a conserved TBC domain. Domain deletion analysis showed that the TBC domain, C- and N-terminal regions of FgGyp8 are all important for its biological functions in F. graminearum. Moreover, we showed that FgGyp8 catalyzes the hydrolysis of the GTP on FgRab1 to GDP in vitro, indicating that FgGyp8 is a GTPase-activating protein (GAP) for FgRab1. In addition, we demonstrated that FgGyp8 is required for FgSnc1-mediated fusion of secretory vesicles with the plasma membrane in F. graminearum. Finally, we showed that FgGyp8 has functional redundancy with another FgRab1 GAP, FgGyp1, in F. graminearum. Taken together, we conclude that FgGyp8 is required for vegetative growth, conidiogenesis, pathogenicity and acts as a GAP for FgRab1 in F. graminearum.